Child Marriage and Gender-Based Violence in Uganda - Awich Ochen, Eric; Nanfuka, Esther; Turyomurugyendo, Florence; Jones, Adele; Wager, Nadia; Cumming, Roslyn (Uganda None, 2021)
This Policy Brief is drawn from qualitative research carried out in 2018 in Uganda, by the None in Three Research Centre Uganda (www.noneinthree.org /uganda/ ) . The research involved in-depth interviews with 45 survivors of child marriage and gender-based violence and focus groups with men and youth (including convicted perpetrators of violence) as well as members of the community.